Face Recognition Approach in the Observance of Faculty Attendance System With Voice Command - Jamielyn Fernandez; Jefferson Fernandez; Carmela Perez; Francis Tucay; Ferdinand Dalisay (Southeast Asian Journal of Science and Technology, 2021)
To respond to the pandemic, faculty attendance is made paperless through face recognition and voice command.  This study aimed to develop an approach in the observance of faculty attendance of schools using face recognition scanners or web cameras.  The study Face Recognition Approach in the Observance of Faculty Attendance System with Voice Command attained the following: (1) to identify the challenges encountered in the manual attendance system, (2) to determine the appropriate features of the developed system and (3) to establish the security measures of the developed system. In developing the system, the Rapid Application Development was applied.  The developed system makes used of Python, Bootstrap, HTML, and CSS. The developed system offers easy to understand directions and user-friendly interface.  It generates reports such as daily time records.   It can perform in a minimal amount of time given that the system has a voice command feature. It also handles the records and information giving the users convenience and redirecting their time to a more productive work.  In addition, the developed system provides easy and fast searching of information.  The developed system proved to be efficient in monitoring faculty attendance.